2019
DOI: 10.3390/nu11030595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fresh Watermelon Consumption on the Acute Satiety Response and Cardiometabolic Risk Factors in Overweight and Obese Adults

Abstract: Although some studies have demonstrated the beneficial effects of watermelon supplementation on metabolic diseases, no study has explored the potential mechanism by which watermelon consumption improves body weight management. The objective of this study was to evaluate the effects of fresh watermelon consumption on satiety, postprandial glucose and insulin response, and adiposity and body weight change after 4 weeks of intervention in overweight and obese adults. In a crossover design, 33 overweight or obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…( 34 ) , who applied arginine supplementation (3 g day –1 ) in prediabetic patients for 8 weeks. However, watermelon consumption (2 cups day –1 ) by overweight or obese subjects for 4 weeks did not change the antioxidant enzyme ( 35 ) . Most of the available animal studies have revealed the positive effects of citrulline, arginine and watermelon on the levels of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…( 34 ) , who applied arginine supplementation (3 g day –1 ) in prediabetic patients for 8 weeks. However, watermelon consumption (2 cups day –1 ) by overweight or obese subjects for 4 weeks did not change the antioxidant enzyme ( 35 ) . Most of the available animal studies have revealed the positive effects of citrulline, arginine and watermelon on the levels of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, in another trial, arginine supplementation at 3 g day –1 in obese patients with prediabetes for 8 weeks elevated the TAC level ( 34 ) . Similarly, in a cross‐over study on obese or overweight adults, the consumption of watermelon (2 cups day –1 ) for 4 weeks increased TAC levels ( 35 ) .…”
Section: Discussionmentioning
confidence: 98%
“…Watermelon is a diuretic and contains large amounts of β-carotene, a precursor of Vitamin A (Naz et al 2014). The watermelon fruit is effective in reducing cancer, cardiovascular disorders, diabetes, blood pressure and obesity (Edwards et al 2003;Naz et al 2014;Lum et al 2019). The quantitative assessment indicates that watermelon has 46% calories, 20% vitamin C and 17% vitamin A and has higher lycopene than tomato (Biswas et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Watermelon contains a variety of other phytochemicals that have beneficial effects on human health, including dietary fiber, vitamin C, vitamin E, β-carotene, lycopene, and flavonoids ( 12 ). Consequently, other benefits of watermelon have recently been studied, including increased satiety and glucose tolerance ( 13 ) and decreased LDL and total cholesterol ( 14 ).…”
Section: Introductionmentioning
confidence: 99%